Games independentes: fundamentos metodológicos para criação, planejamento e desenvolvimento de jogos digitais - Lemes, David de Oliveira (2009)
The following research gathers and analyses the methodological elements for creation, production and development of digital games with a focus on the independent game producer. It elapses over the fundamental characteristics of digital games to underlie the theme to be studied, it seeks to report briefly the history of games and characters when talking about questions related to game creation. It pursuits to systematize the main questions over planning digital games as the game design and the project management, the creation and the character design, progression, difficulty, playability, applied script to the game universe, programming languages and software libraries. The production of game design focus practical and technological aspects, starting on interface design for games, 3D modelling in its main aspects, as objects, scenarios and game developed tridimensional worlds, the production of 2D images as textures and similarities, it seeks to situates the sound environment in the digital game universe until it reaches the game engine, reporting its main features for game production